High Versus Low Ligation of the Inferior Mesenteric Artery During Rectal Resection for Cancer: Oncological Outcomes After Three Years of Follow-Up From the HIGHLOW Trial. Issue 2 (19th December 2020) - Mari, Giulio M.; Crippa, Jacopo; Achilli, Pietro; Montroni, Isacco; Ugolini, Giampaolo; Taffurelli, Giovanni; Cocozza, Eugenio; Borroni, Giacomo; Valenti, Francesco; Roscio, Francesco; Ferrari, Giovanni; Origi, Matteo; et al.
Abstract : Objectives: To determine the disease-free survival (DFS), disease-specific survival (DSS), and recurrence in patients who underwent laparoscopic low anterior rectal resection with total mesorectal excision (TME) with either high or low ligation of the inferior mesenteric artery (IMA). Background: The level of IMA ligation during anterior rectal resection with TME is still a matter of debate, especially in terms of oncological adequacy. Methods: Between June 2014 and December 2016, patients scheduled to undergo elective laparoscopic low anterior resection (LAR) and TME in 6 Italian nonacademic hospitals were randomized into 2 groups in the HIGHLOW Trial (ClinicalTrials.gov Identifier: NCT02153801) according to the level of IMA ligation: high ligation (HL) versus low ligation (LL). DFS, DSS, and recurrence were inquired. Recurrence was determined at 3, 6, 9, and 12 months and every 6 months thereafter. Patients and tumor characteristics as well as surgical outcomes were analyzed to identify risk factors for recurrence. Results: One hundred ninety-six patients from the HIGHLOW trial were analyzed. Median follow-up for DFS was 40.6 (interquartile range [IQR], 6–64.7) and 40 (IQR, 7.6–67.8), while median follow-up for DSS was 41.2 (IQR, 10.7–64.7) and 42.7 (IQR, 6–67.6) in the HL and LL groups, respectively. The 3-year DFS rate of HL and LL patients was 82.2% and 82.1% ( P = 0.874), respectively. The 3-year DSS for HL and LL patients was 92.1% and 93.4% ( P = 0.897), respectively. There was no statistically significant difference in the local recurrence rate (2% HL vs 2.1% LL), in the regional recurrence rate (3% HL vs 2.1% LL), and in the distant recurrence rate (12.9% HL vs 13.7% LL). Multivariate analysis found conversion to open surgery (hazard ratio [HR], 3.68; P = 0.001) and higher stage of disease (HR, 7.73; P < 0.001) to be significant determinant for DFS. Conclusions: The level of inferior mesenteric artery ligation during LAR and TME for rectal cancer does not affect DFS, DSS, and recurrence. Abstract : Mini-Abstract Disease-free survival (DFS), disease-specific survival (DSS), and recurrence were assessed among rectal cancer patients who underwent laparoscopic low anterior resection (LAR) with total mesorectal excision (TME) with either high or low ligation of the inferior mesenteric artery (IMA). A total of 196 patients from the HIGHLOW trial were analyzed. The level of inferior mesenteric artery ligation during LAR and TME for rectal cancer did not affect DFS, DSS, and recurrence.